2018
DOI: 10.3934/publichealth.2018.3.203
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of malnutrition based on anthropometry among primary schoolchildren in Binh Dinh province, Vietnam in 2016

Abstract: ObjectiveThe study was conducted to determine the prevalence of malnutrition based on anthropometry among primary schoolchildren in Binh Dinh province, Vietnam.Material and MethodsThis was a school-based cross-sectional survey using random sample technique with multistage process. Variables in malnutrition were classifed as thinness, stunting, underweight, overweight, and obesity based on z-scores according to the World Health Organization (WHO) (2007). Anthropometric measurements were taken according to WHO's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…A randomized controlled trial [ 29 ] in India to determine impact of nutritional education/ counselling proved that counselling provided by health care workers through existing primary healthcare services was effective in improving anthropometry, reducing illness episodes and increasing daily calorie intake in all groups enrolled. Which was also observed in a Vietnamese study by Pachon [ 19 ] 105 children with mild malnutrition at inclusion, reduced to 82 while 4 entered the normal category. Their mean daily calorie, protein intake increased.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A randomized controlled trial [ 29 ] in India to determine impact of nutritional education/ counselling proved that counselling provided by health care workers through existing primary healthcare services was effective in improving anthropometry, reducing illness episodes and increasing daily calorie intake in all groups enrolled. Which was also observed in a Vietnamese study by Pachon [ 19 ] 105 children with mild malnutrition at inclusion, reduced to 82 while 4 entered the normal category. Their mean daily calorie, protein intake increased.…”
Section: Discussionsupporting
confidence: 69%
“…Socioeconomic inequality in malnutrition among children has been documented by various studies from India [ 16 ], South Africa [ 17 ], China [ 18 ] and Ghana [ 8 ]. A Vietnamese study, reported highest prevalence of adverse nutritional status in socio economically deprived mountainous, midland areas [ 19 ]. A Nigerian study reported that childhood malnutrition was associated with poor socioeconomic status, defined by poor maternal income and their dwelling type was in a 1-bedroom household [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is a general term that refers to two distinct conditions as under-nutrition and overweight. Undernutrition includes stunting, wasting, and being underweight, whereas overweight/obesity is associated with a number of non-communicable diseases (diabetes, cancer, stroke, and heart disease) [ 1 – 3 ]. According to the WHO, approximately 1.9 billion adults worldwide were overweight, while 462 million were underweight.…”
Section: Introductionmentioning
confidence: 99%
“…There were lots of studies about U5 malnutrition around the world. In previous studies, they focused only on the identification of the risk factors of malnutrition using classical model like logistic regression [ 1 – 3 , 11 21 ]. Therefore, it is necessary to propose a predictive model on the identified the significant risk factors for predicting malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The stunting malnutrition prevalence has also declined from 29.3% to 24.2% (2010)(2011)(2012)(2013)(2014)(2015). While underweight has dropped rapidly (> 60%) compared to 1990, the obesity prevalence in children (< age 5) is growing rapidly [6].…”
mentioning
confidence: 99%